Effects of nutritional interventions on nutritional and functional outcomes in geriatric rehabilitation patients: a systematic review and meta-analysis - Wijngaarden, Janneke Petra van; Wojzischke, Julia; van den Berg, Claudia; Cetinyurek-Yavuz, Aysun; Diekmann, Rebecca; Luiking, Yvette C.; Bauer, Jürgen M. (Journal of the American Medical Directors Association, 2020)
Objectives - It has been recognized that nutritional interventions play a role in improving the nutritional and functional status of older persons. This systematic review summarizes the evidence on nutritional and functional outcomes of nutritional interventions alone or in combination with physical exercise in geriatric rehabilitation patients. - Design - Eight electronic databases were searched until July 1, 2019 to identify nutritional intervention studies in patients aged ≥60 years who were admitted to geriatric rehabilitation. A meta-analysis was performed to quantify intervention effects on serum albumin, muscle mass, and hand grip strength (HGS). - Results - A total of 1962 studies were screened and 13 included in the systematic review. Studies were heterogeneous in interventions (4 nutritional interventions, 6 physical exercise + nutritional intervention, 1 timing of protein provision, 1 exercise + dietary advice, 1 nutrition-related nursing care) and outcomes. Among the 9 interventions that tested oral nutritional supplements (ONS) with protein, with or without exercise, 7 studies reported protein intake and 6 showed increased protein intakes, 2 of 5 studies showed increased albumin levels, and 5 of 9 reported an improvement in functional outcomes (BI, Functional Independence Measure, mobility). Meta-analyses showed no significant intervention effects on albumin [standardized mean difference (SMD) 0.45, 95% confidence interval (CI) −0.14, 1.04 (4 studies)], muscle mass [mean difference (MD) 2.14 kg, 95% CI -2.17, 6.45 (3 studies)], and HGS [SMD -0.04, 95% CI -0.55, 0.63 (3 studies)], but was based on a very limited number of studies. - Conclusions and Implications - Only a limited number of studies with heterogeneous nutritional interventions and outcomes were available in the geriatric rehabilitation population. Studies that included ONS improved nutritional outcomes, especially protein intake and albumin levels. Functional outcomes improved in the majority of reporting studies. This indicates benefits of protein supplementation, with or without exercise, in this population. Future well-designed and well-powered clinical trials are needed to clarify existing controversial aspects.